Cyber moder of electronic commerce acustomer centric - Němcová, Zuzana; Dvořák, Jiří; Budík, Jan (Univerzita Pardubice, 2011)
This paper describes how to implement methods of cybernetics into the economy. The mathematical model was created in MATLAB software. Created model works with two feed backs, which are realized through question forms. The goal of this model is to decrease difference between demand and offer.
Keywords: electronic commerce; strategy; technology; marketing; E-commerce; business to customer; business to business